Characterization of Wastewater in The University Campus: A Case Study in Universitas Andalas, Indonesia - Ruslinda, Yenni; Nur, Ansiha; Komala, Puti Sri; Leni, Leni; Regia, Rinda Andhita; Mardatillah, Regina (Dampak, 2024)
This study aims to analyze wastewater characteristics at Universitas Andalas Campus Limau Manis Padang encompassing physical, chemical, and biological attributes, while comparing them to established quality standards and estimating mass loading. Wastewater samples were collected from various sources, including domestic and specific wastewater. Sampling locations and times were chosen based on peak activity. Physical analysis revealed temperature ranging from 27.32 to 31.5°C and TSS concentrations from 130.00 to 580.00 mg/L. Chemical parameters displayed significant variation, with pH values between 2.27 and 9.70, BOD5 concentrations spanning 108.46 to 506.59 mg/L, COD levels from 162.70 to 1,428.00 mg/L, and oil and grease content from 0.20 to 84.31 mg/L. N-total ranged from 47.07 to 309.16 mg/L, sulfate from 72.70 to 1,480.00 mg/L, and phosphate from 1.14 to 98.15 mg/L. Biological attributes showed total coliform counts exceeding 10,000 colonies per 1,000 mL, all surpassing quality standards. Notably, the BOD5/COD ratio indicated low biodegradable quality (values <0.5) for certain wastewater sources. Greywater emerged as the primary pollutant, with substantial mass loadings. Eventually, this study underscores the vital need for wastewater treatment before environmental discharge.Keywords: Characteristics, Domestic Wastewater, Campus, Quality Standards, Hazardous Wastewate